Pendampingan Pengelolaan Keuangan dan Manajemen Usaha Pada Bisnis Rumah Makan Daerah Cikarang Selatan - Widiastuti Widiastuti; Zulfa Zakiatul Hidayah; Erna Apriani; Sunita Dasman; Dwi Epty Hidayaty (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
A business can survive if it has good financial knowledge. Financial management and business knowledge have always been the foundation. Along with the times, especially in the digitalization era, it is unfortunate when business people ignore the financial aspects and optimization of their business management. When the company's human resources are able to adjust to the changing times in industry 4.o, then financial management can be done. The purpose of this activity is to assist and provide consultation to business owners in one of the nasi padang restaurants in Cikarang. We come from an environment where business people do not know much about financial education and how to build a business so that it can grow and adapt to digital developments, as well as the lack of training and education provided for business people, especially for micro businesses. The focus of this community service activity is to assist business actors from business management to finance, so as to maximize the ability of their human resources, which is very much needed by business actors who have high competitiveness in this digital era. In the end, it is expected to provide solutions that allow business actors to optimize all business activities in increasing profits and sales, so that the business can survive and develop.